PENGENALAN PEMASARAN ONLINE KERUPUK KERITING PADA PABRIK KERUPUK BAHAGIA KELURAHAN KEBUN TEBENG KECAMATAN RATU AGUNG KOTA BENGKULU - Ssetiawan, Youngky; Afriani, Sulisti; Yanti, Rina Trisna; Herlin, Herlin; Yustiantianti, Nirta Vera (STIA Bengkulu, 2025)
The introduction of the marketplace aims to add a new online marketing strategy for the curly cracker factory in Kebun Tebeng Village, Ratu Agung District, Bengkulu City in order to expand the marketing network and increase income turnover in sales. Data collection uses observation, interviews and documentation methods. The curly cracker factory began producing and selling its products in 2010. Initially, the cracker factory was selling crackers by utilizing marketing from customers through word of mouth and stall to stall. To increase sales of curly cracker products, this cracker factory needs another alternative to market its products so that it can expand its network by introducing products through the marketplace (Facebook). Using the marketplace platform is not only profitable for the Krupuk Factory itself, but with the training and knowledge provided, Krupuk factory employees can also directly experience the benefits of using the marketplace platform.